Interplay among institutional actors for sustainable economic development—Role of green policies, ecoprenuership, and green technological innovation - Wang, Xinxin; Javaid, Muhammad Umair; Bano, Sobia; Younas, Hamna; Jan, Amin; A. Salameh, Anas (Frontiers in Environmental Science, 2022)
This study conceptualizes the effect of green economy policies i.e., green fiscal policy, green investment, and green jobs on sustainable economic development through direct and serially mediated paths. Ecopreneurship and Green technological innovation have been perceived/recognized as potential mediators linking green economy policies to sustainable economic development. The conceptual model shed lights on the integrated role of two main actors - the government of the state and its market forces in moving forward towards the goal of sustainability and gains for all. It is presented that incorporating ‘green’ into public policy creates suitable environment for green entrepreneurs to come up with innovative green technologies and sustainability led business models. Theoretically supported by Institutional theory, this paper aims to contribute to sustainability transition research by focusing on the collective role of different institutional forces in achieving economic gains through sustainability lens.